De Grazia : the Man and the Myths. - Johnson, James W. (University of Arizona Press, 2014)
"This is the first comprehensive biography of Ted DeGrazia, the Tucson artists known as much for his colorful paintings of the Southwest and Mexico as his eccentric personality. De Grazia: The Man and the Myths mines private archival sources, memoirs, and interviews to draw an intriguing new portrait of this western legend"--